Tribological behaviour of Ni/WC–MoS2 composite coatings prepared by jet electrodeposition with different nano-MoS2 doping concentrations. (January 2023) - Ren, Anhua; Kang, Min; Fu, Xiuqing
Graphical abstract: Highlights: Ni/WC-MoS2 composite coatings were deposited on 45 steel using the jet electrodeposition. The effect of doping by MoS2 on composite coatings' surface morphology and tribological behaviour was investigated. Appropriate doping by MoS2 facilitated the deposition and distribution of WC particles in the composite coating. The wear mechanism of the Ni/WC-MoS2 composite coating was analysed under dry friction conditions. The lubrication mechanism of MoS2 -doped composite coatings during wear was investigated. Abstract: Ni/WC-MoS2 composite coatings were fabricated in electrolytes with different MoS2 doping levels using jet electrodeposition. We investigated the surface characteristics of Ni/WC-MoS2 composite coatings, including the composition, surface morphology, microhardness and tribological behaviour. We also analysed the Ni/WC-MoS2 composite coating wear mechanism during the wear process. The outcomes determined that Ni/WC-MoS2 coatings had better surface quality, smaller grain size and larger coating thickness than Ni/WC coatings. The doping of MoS2 promoted the deposition of WC in the coatings, which further enhanced the microhardness of the coatings. The Ni/WC-MoS2 composite coatings doped at a MoS2 concentration of 5 g/L exhibited a maximal microhardness of 730 HV0.1 . Doping by MoS2 effectively minimized the coefficients of friction ( CoFs ) of the composite coatings to 0.3. During the wear process, the repair effect of MoS2 and formation of oxidised friction films transformed the adhesive wear into oxidative wear assisted by abrasive wear, which improved the abrasion resistance of the coatings and diminished the wear rate. The wear rate of the Ni/WC-5 g/L MoS2 composite coating decreased by 47.34 % in comparison with that of coatings without MoS2 doping, which was 7.44 × 10 4 μm 3 /N∙m. The findings indicate that doping MoS2 can effectively enhance the surface wear resistance. This research provides a practical approach to prolong the service life of metal parts.